Optimizing Strategies for Electronic Catalog E‑Purchasing in Government Goods/Services Procurement in Musi Rawas Utara Regency - Wuri Setianingrum; Dwi Rachmina; A. Faroby Falatehan (Dinasti Publisher, 2025)
This study is motivated by the low utilization of electronic catalog–based e-purchasing in government goods and services procurement in Musi Rawas Utara Regency. This condition indicates the need for strengthening strategies to optimize the implementation of electronic catalog e-purchasing policies. The aims of this study are to analyze the implementation of electronic catalog e-purchasing policies, examine the roles of the stakeholders involved, and formulate optimization strategies for electronic catalog e-purchasing in Musi Rawas Utara Regency. This research employed a qualitative descriptive approach, with data collected through questionnaires and interviews with procurement officials and local business actors. The analysis was conducted using a policy implementation model, internal and external factor analysis, SWOT, and QSPM. The findings show that the implementation of electronic catalog e-purchasing in Musi Rawas Utara Regency has been carried out effectively, with respondents showing generally positive perceptions. However, several areas for improvement were identified, including the need for more equitable policy dissemination, strengthened digital infrastructure, enhanced implementer motivation, enforcement of fairness for business actors, an increased number of local suppliers in the electronic catalog, and improved oversight and information services. The study further reveals that the success of optimization is influenced by the commitment of regional leadership, the readiness of human resources, and coordination among stakeholders. The resulting priority strategies include strengthening regional commitment and policy frameworks, advancing procurement-related public communication and outreach, improving human resource capacity and digital literacy, and empowering local business actors through digital-based initiatives.